Reporting a case of isolated levocardia - Heydarian, Tahereh; Allahdadian, Maryam (Journal of Shahrekord University of Medical Sciences, 2025)
Isolated levocardia with situs inversus is a rare congenital anomaly characterized by the abnormal positioning of the heart and abdominal organs. This condition is frequently associated with congenital heart defects and typically carries a poor prognosis. Accurate diagnosis and effective management are crucial for improving clinical outcomes. This report presents a case involving a 25-year-old woman in her first pregnancy who underwent a routine ultrasound at 17 weeks and 2 days of gestation. The ultrasound revealed dextrocardia with situs inversus, prompting a referral to a pediatric cardiologist. Subsequent echocardiography at 18 weeks confirmed the presence of the stomach on the right side and a reversed heart axis, leading to a diagnosis of isolated levocardia with atrioventricular septal defects (AVSDs). The pregnancy was medically terminated at 19 weeks, following appropriate medical approval.